Preparation and standardisation of ramban ras (W.S.R. bhaishajya ratnavali) - Mahesh Chandra; Sourmi; G.K. Saxena; Neelam Sahu; Pankaj Thakur; Anjali Tamori (International Journal of Pharmacy and Analytical Research, 2022)
Ramban Rasa is described in the various texts in Ayurveda. Here the study is carried out on the Ramban Rasa mentioned in Bhaishajya Ratnavali (10/90-92). Ramban Rasa is used to cure the diseases like, Grahni, Amvata, and Agnimandhya. In the present work – 3 samples of Ramban Rasa A,B & C is prepared by the method given in the Bhaishajaya Ratnavali (10/90-92) .The ingredient of Ramban Rasa is Parad, Gandhak, Vatsanabh, Lavang, Marich, Jayphal and bhavna dravya is imli swarasa.After the preparation of 3 samples of Ramban Rasa A, B & C, their physiochemical analysis was done and compared. The parameters are taken for physiochemical analysis / standardization are:- 1. Physical Analysis according to Ayurveda- Shabda, Sparsha, Roop, Rasa & Gandha pariksha. 2.Chemical Analysis of Ramban Rasa like pH value, Moisture content, Ash content, Acid Insoluble ash, Water soluble extractives, Alcohol soluble extractives, A.A.S for heavy metals like chromium, cadmium, copper, lead, nickel, manganese, cobalt, arsenic & mercury. These samples of Ramban Rasa contain heavy metals less than one ppm.